The Effects of Oil Price Volatility and Trade Intensity on Renewable Energy Consumption in Oil-Importing Countries - Eghbal Manesh, Fatemeh; Nesabian, Shahriar; Mahmoodzadeh, Mahmood; Daghighi Asli, Alireza (Management Strategies and Engineering Sciences, 2025)
The expansion of renewable energy consumption has received special attention due to the increasing limitations of natural resources. This study examines the impact of oil price volatility and trade intensity on renewable energy consumption in oil-importing countries. Accordingly, data from ten major oil-importing countries, including the United States, Japan, China, Germany, the Netherlands, South Korea, Italy, India, France, and Singapore, covering the years 2000 to 2022, have been analyzed. In this study, oil price volatility was measured using the EGARCH method, and the estimation results of the model and relationships between variables were analyzed within the framework of the generalized method of moments (GMM). The results indicate that oil price volatility, with a coefficient of 1.27, trade intensity, with a coefficient of 0.30, innovation, with a coefficient of 0.97, and human capital development, with a coefficient of 0.42, contribute to the increase in renewable energy consumption.